The effectiveness of acceptance and commitment therapy in the quality of life and anxiety of death in women suffering from breast cancer - Rezaei, Sadegh; Omidi, Malihe; Bahrebar, Soroush (Researcher Bulletin of Medical Sciences, 2021)
Objective: The effectiveness of acceptance and commitment therapy (ACT) in quality of life and death anxiety in women suffering from breast cancer. Materials and Methods: This study was a quasi-experimental research with a non-equivalent control group design. All women suffering from breast cancer and being treated at Imam Khomeini Hospital in year 2019. The sample was randomly selected. Thirty people were selected 15 of whom were randomly assigned to the experimental group and 15 were randomly assigned to the control group. During eight 90-minute sessions, the experimental group received the ACT intervention. Both groups were evaluated before and after the intervention with quality of life questionnaires and death anxiety, and multivariate analysis of covariance and variance was used to analyze the data. Data analysis was performed with SPSS24. Results: The findings suggested that the quality of life and death anxiety in the experimental group were significantly different from the control group. Conclusion: The training program based on ACT had an impact on the quality of life and death anxiety of women suffering from breast cancer.